Transcriptomic analysis of a transgenic zebrafish hepatocellular carcinoma model reveals a prominent role of immune responses in tumour progression and regression. Issue 7 (4th March 2014) - Li, Zhen; Luo, Huaien; Li, Caixia; Huo, Xiaojing; Yan, Chuan; Huang, Xiaoqian; Al‐Haddawi, Muthafar; Mathavan, Sinnakaruppan; Gong, Zhiyuan
Abstract : Using our previously established xmrk transgenic zebrafish, hepatocellular carcinoma (HCC) was generated by induced expression of xmrk, which encoded a hyperactive epidermal growth factor receptor (EGFR) homolog, and regressed by suppression of xmrk expression. To investigate molecular changes in liver tumour progression and regression, RNA‐Seq was performed for induced HCC and early and late stages of liver tissues during tumour regression. We found that Xmrk‐induced zebrafish HCC shared strong molecular characteristics with a human HCC subtype (S2), which shows activated Myc signalling, upregulated phosphor‐S6 and epithelial cell adhesion molecule. In the HCC stage, there were enhanced proteasome, antigen processing and presentation, aminosugars metabolisms, p53 and cell cycle pathways. During tumour regression, the transcriptomic profile showed a reversed trend of molecular changes compared with human HCC progression. Interestingly, distinct immune responses in tumour progression and regression were observed, including increased major histocompatibility complex class I (MHCI) at the HCC stage, enriched immune cell trafficking signals and inflammation in early regression and enhanced MHCII in late regression. Both neutrophils and macrophages were enriched during tumour progression and regression; however, the distribution of neutrophils and macrophages in HCC was relatively uniform, whereas both types of immune cells were regionally clustered during tumour regression, especially with dominant blood vessel association of macrophage in late regression, suggesting differential functions of these immune cells in tumour progression and regression. As tumour regression in our model resembles the targeted inhibition of EGFR in cancer therapy, our observations may provide molecular insights into the targeted inhibition and highlight the importance of immune response in tumour regression. Abstract : What's new? Spontaneous regression of hepatocellular carcinoma (HCC) is a rare event in humans, but identification of its underlying mechanism could help advance cancer therapy. In the present study, application of RNA‐Seq analysis to HCC progression and regression in zebrafish shows that molecular changes during tumor regression are reversed when compared with HCC progression. Distinct immune responses were observed for tumor progression versus regression, indicating that the immune system plays an important role in HCC tumor behavior. The findings may also offer insight into the importance of immune responses during targeted EGFR inhibition in cancer therapy.